Towards more effective advanced drug delivery systems - Crommelin, Daan J.A.; Florence, Alexander T. (International journal of pharmaceutics, 2013)
This position paper discusses progress made and to be made with so-called advanced drug delivery systems, particularly but not exclusively those in the nanometre domain. The paper has resulted from discussions with a number of international experts in the field who shared their views on aspects of the subject, from the nomenclature used for such systems, the sometimes overwrought claims made in the era of nanotechnology, the complex nature of targeting delivery systems to specific destinations in vivo, the need for setting standards for the choice and characterisation of cell lines used in in vitro studies, to attention to the manufacturability, stability and analytical profiling of systems and more relevant studies on toxicology. The historical background to the development of many systems is emphasised. So too is the stochastic nature of many of the steps to successful access to and action in targets. A lacuna in the field is the lack of availability of data on a variety of carrier systems using the same models in vitro and in vivo using standard controls. The paper asserts that greater emphasis must also be paid to the effective levels of active attained in target organs, for without such crucial data it will be difficult for many experimental systems to enter the clinic. This means the use of diagnostic/imaging technologies to monitor targeted drug delivery and stratify patient groups, identifying patients with optimum chances for successful therapy. Last, but not least, the critical importance of the development of science bases for regulatory policies, scientific platforms overseeing the field and new paradigms of financing are discussed.